Samsung Electronics Corporation Leadership In Diversified Technological Business - Chew, Suan Choo (2005)
Samsung Electronics was founded in the early 70s. The success that Samsung Electronics achieved is a result of the corporation's strategy in marketing, production, research and development, corporate responsibilities, management style and structure, adopting just-in-time (JIT) and supply chain management (SCM) , and others.